The role of a learning approach in building an interorganizational network aiming for collaborative innovation - Ystrom, Anna et al (2019)
Collaboration has become a common way for organizational actors to engage in problem solving and innovation. Yet shifting from strategic interactions (driven by reduction of transaction costs) to transformational interaction (driven by collaborative transorganizational development) appears to be difficult to achieve in practice in a network setting. This article argues that such a shift can be enhanced by adopting an action learning approach, which entails working on real-life problems without clear solutions and collectively working to resolve them. Based on an action learning research process, this article therefore explores ways to support collective knowledge creation within an interorganizational network setting. It provides rich illustrations of how the interactions in the network changed through the process, and the participants moved from a space of territorial protection to a space for collaborative exploration. From this case, the article outlines a model for learning in interorganizational networks and discusses related challenges. - Reproduced.